Aksentuasi Nilai Insaniyah dalam Film Animasi Keluarga Somat - Muhammad Saefullah; Maryono Maryono; Robingun Suyud El Syam (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This article aims to describe the accentuation of the value of Insaniyah in the Somat Family Animation Film, where previous research has not been specific to this aspect. Qualitative setting with descriptive analysis is a form of this research, in order to describe the problem as findings from data in manuscripts and related writings. The findings show that the film has a storyline that is easy to digest, contains many human values and characters that are so attached to the reality of daily life. The implications of research on the importance of practicing human values in animated films for Islamic education. Research is expected to contribute to the meaning of a film from the aspect of social ethics.